Effect of vertical reinforcing bars on formwork pressure of SCC containing recycled aggregates. (September 2017) - Matar, Pierre; Assaad, Joseph J.
Abstract: The feasibility of self-consolidating concrete (SCC) containing recycled concrete aggregate (RCA) was demonstrated in structural civil engineering applications. Yet, limited information exists regarding the effect of RCA additions, especially in presence of steel reinforcement, on lateral pressure exerted on formworks. This paper reports experimental data obtained from twenty-one SCC mixtures cast in 200 × 400 × 1600-mm formwork containing up to 4.71% vertical steel (the spacing between transverse steel was set to 450 mm). Test results have shown that mixtures incorporating RCA exhibited reduced initial pressure, which was mostly attributed to higher aggregate surface roughness that increases internal friction. The decrease in pressure was accentuated with the increase in vertical steel density, suggesting that the reinforcement cage confines the plastic concrete and carries part of its load. Special emphasis was placed to develop conservative reinforcement indices for appropriate prediction of SCC pressure, as well as propose modifications for existing models to account for the effect of RCA additions and presence of vertical steel bars.